A novel antennal form in trilobites. (January 2023) - Edgecombe, Gregory D.; Fortey, Richard. A.
Abstract: Known antennae of trilobites are all flagelliform, in marked contrast to the varied first antennae of marine pancrustaceans. An exceptionally preserved specimen of the Early Ordovician (late Tremadocian) asaphid Asaphellus tataensis Vidal, 1998, from the Fezouata Shale in Morocco, exhibits both antennae in situ; they are relatively short, widen distally, and bear a series of round, dome-shaped organs along both their dorsal and ventral surfaces. These organs are vastly larger than chemo- or mechanosensory sensilla on the antennae of other arthropods, rendering their homology and function uncertain. The clavate antennae of Asaphellus reveal the furthest deviation from the inferred ancestral state of the trilobite antenna known to date. This could be an adaptation for detection of prey, because most Asaphidae have been claimed as predators and scavengers on the basis of specialized features of the calcified exoskeleton.